1996
DOI: 10.1007/s003840050059
|View full text |Cite
|
Sign up to set email alerts
|

Enteric innervation in idiopathic megarectum and megacolon

Abstract: We have studied the resection specimens from 5 patients with idiopathic megarectum and megacolon and 10 control subjects with non-obstructing colonic cancer. Histological staining with haematoxylin and eosin, and immunocytochemical staining for protein gene product 9.5 (PGP9.5), S100 protein, vasoactive intestinal polypeptide (VIP) and calcitonin gene-related peptide (CGRP), and histochemical localization of NADPH diaphorase was performed. The amount of VIP and CGRP present in samples was measured using an enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 33 publications
0
23
1
Order By: Relevance
“…1,[15][16][17] It has been suspected for many years that pathologic changes in the enteric nervous system could be involved in the pathophysiology of STC. 2,3, 18 Bassotti et al 17 reported that mass movements occur less frequently in patients with STC. However, their propulsive waves were of normal amplitude, which suggests an abnormality of neural initiation rather than of the colonic muscle itself.…”
Section: Discussionmentioning
confidence: 98%
“…1,[15][16][17] It has been suspected for many years that pathologic changes in the enteric nervous system could be involved in the pathophysiology of STC. 2,3, 18 Bassotti et al 17 reported that mass movements occur less frequently in patients with STC. However, their propulsive waves were of normal amplitude, which suggests an abnormality of neural initiation rather than of the colonic muscle itself.…”
Section: Discussionmentioning
confidence: 98%
“…This protein is involved in the ubiquitin-proteasome system, which is a major pathway for selective protein degradation (Hershko and Ciechanover, 1992), thereby forming an essential part of the normal cellular processes in the cells where it is present. The human disorders where this protein has been used as part of the investigation include conditions such as Hirschprung's disease (Sams et al, 1992;Oh et al, 2002) and idiopathic megarectum and megacolon (Gattuso et al, 1996(Gattuso et al, , 1997. These studies demonstrated a significant reduction in labelled neurons in the affected areas of intestine as well as documenting that PGP 9.5 provides a reliable and sensitive means of identifying neurons in the intestinal tract (Sams et al, 1992;Gattuso et al, 1996Gattuso et al, , 1997Oh et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The human disorders where this protein has been used as part of the investigation include conditions such as Hirschprung's disease (Sams et al, 1992;Oh et al, 2002) and idiopathic megarectum and megacolon (Gattuso et al, 1996(Gattuso et al, , 1997. These studies demonstrated a significant reduction in labelled neurons in the affected areas of intestine as well as documenting that PGP 9.5 provides a reliable and sensitive means of identifying neurons in the intestinal tract (Sams et al, 1992;Gattuso et al, 1996Gattuso et al, , 1997Oh et al, 2002). PGP 9.5 has also been shown to be a useful general marker for enteric neurons in recent horse studies, both in health and disease (Milne et al, 2005;Chiocchetti et al, 2009a, b).…”
Section: Discussionmentioning
confidence: 99%
“…Other inflammatory processes, such as psoriasis, arthritis, and asthma involve increased substance P immunoreactivity of sensory nerves (Levine et al 1985;Naukkarinen et al 1989;Ollerenshaw et al 1991). Unfortunately, we could not address this question directly in our material because the neurochemical indentification of sensory nerves, i.e., co-localization of substance P and CGRP, does not hold for human gut (Gattuso et al 1996;Sjölund et al 1997). …”
Section: Discussionmentioning
confidence: 99%